Micromorphology and damage characterization of vacuum brazed stainless steel joints with laser etched interfaces - Jie Wang; Huixin Chen; Yichuan Wang; Nian Li; Xinlong Wei; Xiang Ling (Materials Research Express)
This study investigates the effect of laser etching on vacuum welded joints through organizational observation and shear testing. The residual stress in various sample structures during the brazing process was analyzed through the proposed FE models. The findings indicate that laser etching improves the wetting behavior of copper brazing material on AISI 304 stainless steel substrate. However, contrary to theoretical expectations, due to the melting and splashing of the base material during laser etching, loose stacked particles are formed. With the increase of laser etching times, the shear strength of brazed joints shows a gradual decline trend. The finite element results indicate that the microstructure formed by laser etching promotes the generation of thermal residual compressive stress and reduces residual tensile stress.